REINVENTION IN TIMES OF CRISIS: BRAZILIAN ENTREPRENEURSHIP BOOSTED BY THE COVID-19 PANDEMIC - Sant’Ana, Ana Cláudia de Deus; Campos, Patrícia Carvalho; Dornelas, Myriam Angélica; Costa e Barbosa, Rosemary Pereira; Vieira, Lais Karlina (Seven Editora, 2026)
Considering the relevance of entrepreneurship to the economic and social development of the country, in different sectors of activity, this study sought to examine, through a literature review, how the COVID-19 pandemic influenced the emergence of new entrepreneurs in Brazil. Furthermore, it aimed to identify the segments that stood out most during this period and the main challenges faced by new entrepreneurs. The justification for this research is based on the importance of understanding the role of entrepreneurship in crisis contexts, especially in the face of adverse scenarios that demand innovation, resilience, and adaptation. The research, of a qualitative and descriptive nature, was structured through an integrative review of scientific production published between 2020 and 2024. The content analysis of the studies sought to identify, select, evaluate, and synthesize the evidence on the growth of entrepreneurship in Brazil impacted by the COVID-19 pandemic. The results indicated that the pandemic acted as an accelerator for the emergence of new entrepreneurs in Brazil, driven mainly by income loss, unemployment, and the need to adapt to the digital market. It was concluded that, despite the difficulties imposed by the health crisis, the pandemic context fostered both necessity-driven and opportunity-driven entrepreneurship, strengthening innovation and reinvention in small businesses.